Re-Building Strategies Adopted By The Hospitality Sector In The Post Covid 19 Period ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: The Novel Coronavirus shock affected impacted the entire world. It affected the hospitality sector badly during the pandemic situation. The hotel industry adopted  various strategies to overcome this pandemic situation. Objectives: The study attempts to  find out the conditions and the re-building strategies adopted by the hospitality industry such  as the amenities and facilities provided to the guest and also the safety measures taken by the  hotels during the pandemic situation. Methodology: The study is descriptive in nature.  During the pandemic situation there were several problems faced by the hotel industry. The  various problems were discussed with the operating departmental heads and the other hotel  staff such as executives, associates and job trainees. The primary data was collected from the  hotel staff through questionnaire method using the online platforms like Google forms and it  was send to the respective persons. 250 samples were taken for the study which included core  departmental heads, employees and the trainees of the hotels. Stratified random sampling  techniques were used for collecting the data. The data collected was classified and tabulated.  The data was analyzed by using different statistical techniques like percentage analysis,  Correlation analysis with the help of IBM SPSS Version 23. Results: Safety measures taken  by the departments included restaurants being sanitized; rearranging the furniture for  maintaining a social distancing; the kitchen staffs getting properly sanitized; wearing mask  and gloves. Sterilizing and sanitizing the guest and their belongings before rooming the  guest. The billing system was shifted more towards the electronic mode. The staff guided the  guests to follow the instructions during their stay in the hotel. Conclusion: The hotel  premises including the public areas and the lobby were sterilized and sanitized every two  hours in most hotels. The workers were asked to work in staggered shifts. The guest who  come to visit and stay in the hotel were made to feel safe and comfortable with the services.
Keywords: Epidemic; Pandemic situation; Social distancing; Sterilized; Sanitized